2022
DOI: 10.1136/bmjopen-2022-064733
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of personal finance training for physicians and a proposed curriculum

Abstract: BackgroundMany physicians complete medical school and graduate medical education (GME) burdened by high debt and financial illiteracy. This places them at increased risk for ill-informed financial decisions, which can result in increased stress and anxiety and a lower quality of life. Furthermore, financial concerns impact physicians’ specialty selections and may partly explain the scarcity of primary care practitioners. In response, medical wellness programmes have increasingly sought to offer personal financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(229 reference statements)
0
3
0
Order By: Relevance
“…However, physicians may not be able to have the time and resources to dedicate to nancial literacy curricula. Instead, nancial advisors may be a more accessible and cost-effective resource, however trainees may be opposed to the inherent con ict of interest and would receive commission from selling their nancial products and services (Grewal & Sweeney, 2021;Igu et al, 2022;McKillip et al, 2018;Ogunkua et al, 2022). The preference of physicians as instructors also explains our ndings that residents identi ed physician led nancial blogs and Facebook groups as a major source of nancial advice.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, physicians may not be able to have the time and resources to dedicate to nancial literacy curricula. Instead, nancial advisors may be a more accessible and cost-effective resource, however trainees may be opposed to the inherent con ict of interest and would receive commission from selling their nancial products and services (Grewal & Sweeney, 2021;Igu et al, 2022;McKillip et al, 2018;Ogunkua et al, 2022). The preference of physicians as instructors also explains our ndings that residents identi ed physician led nancial blogs and Facebook groups as a major source of nancial advice.…”
Section: Discussionmentioning
confidence: 84%
“…In our sample of respondents, only 12% had a formal nancial literacy curriculum as a mandatory component of their residency Importantly, our study demonstrates that residents are strongly interested in the implementation of a formal curriculum and that residents wish to have a physician perspective, radiologist or not. Two systematic reviews on current personal nance training programs for medical trainees demonstrated that the majority of the primary studies rely on physician instructors (Igu et al, 2022;Wesslund et al, 2023). It is probable that residents wish to be taught by physicians who have an implicit understanding of their training journey through medical training and can offer guidance as they start their career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation